2007
DOI: 10.1016/j.micromeso.2006.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Macro–mesoporous silicas complex and the carbon replica

Abstract: Novel macroporous silicas with ordered mesoporous wall structures (~15 nm in pore size) have been synthesized by finely balancing the emulsification of the oil phase with the self-assembly of the amphiphilic block copolymers. The nanocasting method was used to produce hierarchically ordered macro-mesoporous carbon materials. These porous materials have potential applications in catalysis, sorption, separation, etc.Keywords: Hierarchy; Macro-mesoporous; Silica; Carbon; Emulsion; Hydrophobic-hydrophilic balance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…The mesoporous silica materials obtained in the straight-chain assisted system can be used as hard templates for the preparation of other mesoporous materials [104,105]. The assistance of -hexane leads to formation of a macromesoporous silica material, which was used as the hard template for the preparation of hierarchically ordered macromesoporous carbon materials [106].…”
Section: Hard Templatementioning
confidence: 99%
“…The mesoporous silica materials obtained in the straight-chain assisted system can be used as hard templates for the preparation of other mesoporous materials [104,105]. The assistance of -hexane leads to formation of a macromesoporous silica material, which was used as the hard template for the preparation of hierarchically ordered macromesoporous carbon materials [106].…”
Section: Hard Templatementioning
confidence: 99%
“…The obtained results demonstrated the applicability of commercially available CPG to produce carbon replica with a well-defined nanoarchitecture. Typical macroporous carbon replica reported in literature have macropores in the size range of 200 nm (Sun et al, 2007; Zhong et al, 2009; Prévot et al, 2011) up to a micrometer (Cai et al, 2006). The reported material with its median pore width being approximately 60 nm was found to be rare in reported literature apart from the work by Eisenberg et al (2016) which reported a median pore width slightly less than 50 nm for their N-doped hierarchical carbon.…”
Section: Resultsmentioning
confidence: 99%
“…In spite of extensive activity in this area, the use of large-pore SBA-15 (LP-SBA-15; pore diameter >12 nm) as a template has been nearly unexplored. To the best of our knowledge, only Sun et al (2007) applied macroporous-mesoporous LP-SBA-15 with d 100 interplanar spacing of ∼14 nm to synthesize an ordered mesoporous carbon (as seen from TEM) that retained the morphology of the template and exhibited narrow pore size distribution (pore diameter ∼6 nm). However, XRD or SAXS data were not reported, so the crucial information about the periodicity and unit-cell size is not available.…”
Section: Resultsmentioning
confidence: 99%
“…2(b), the carbon samples prepared at different infiltration temperatures had similar Type IV adsorption-desorption isotherms. The capillary condensation steps occurred in the relative pressure range from 0.45 to 0.65 and the isotherms leveled off at higher relative pressure, indicating uniform pore structures and low Sun et al (2007) for their macroporous-mesoporous carbon prepared using a similar template. However, these researchers did not report X-ray diffraction/scattering data, so overall periodicity of their carbon is not clear.…”
Section: Resultsmentioning
confidence: 99%